2018
DOI: 10.1007/s40121-018-0186-1
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Clostridium difficile Infection in Japan: A Systematic Review

Abstract: To increase understanding of the epidemiology, risks, consequences and resource utilization of Clostridium difficile infection (CDI) in Japan, a systematic literature review was undertaken of relevant publications from January 2006 to November 2017. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and methods, 55 articles met the criteria for full review. The majority (58%) of studies were from a single site, with the most recent data from 2015. The incidence, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 61 publications
5
30
0
Order By: Relevance
“…The most frequent ribotypes as revealed by PCR for toxin gene-positive strains were 047, 014/0, and 020 in this study. In a previous Japanese study, the ribotypes present at a high frequency were strains 018, 002, 052, and 369 [22]. In other Japanese study, the ribotypes present at a high frequency was strains 449 [17].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The most frequent ribotypes as revealed by PCR for toxin gene-positive strains were 047, 014/0, and 020 in this study. In a previous Japanese study, the ribotypes present at a high frequency were strains 018, 002, 052, and 369 [22]. In other Japanese study, the ribotypes present at a high frequency was strains 449 [17].…”
Section: Discussionmentioning
confidence: 74%
“…In other Japanese study, the ribotypes present at a high frequency was strains 449 [17]. The frequent PCR ribotypes varied by the studies in Japan [17,22]. In the United States, the most frequent PCR ribotypes were strains 002, 014e020, 027, and 053e163 [23], but the most frequent PCR ribotypes were different according to area.…”
Section: Discussionmentioning
confidence: 81%
“…The CDI strain associated with more severe disease, ribotype 027, is rarely identified in Japan, which may help explain the widespread use of MNZ observed in our study [11,28]. Other reasons may include the less user-friendly formulation of oral VCM (supplied as powder in a vial) and the attempt to avoid potential VCM resistance.…”
Section: Discussionmentioning
confidence: 81%
“…A systematic review of published data from 2006 to 2017 found several evidence gaps including information on the treatments used for CDI (for example type, dose and duration) [11]. Most studies investigating CDI treatment in Japan have been conducted at single centers [12e15] or a limited number of hospitals [16,17], providing snapshots of CDI in certain patient subgroups rather than comprehensive reporting of trends in hospital-onset CDI over time.…”
Section: Introductionmentioning
confidence: 99%
“…CD spores can persist in the environment for extreme long time periods and, thus, facilitate nosocomial transmission and outbreaks [5] [6]. Unfortunately, CDIs have become an increasing clinical and financial burden in healthcare settings all over the world [7][8] [9]. Especially severe CDI courses contribute significantly to the morbidity and mortality of affected patients.…”
Section: Introductionmentioning
confidence: 99%